Gambaran Dampak Permainan Game Elektronik Pada Anak Usia Sekolah Di Wilayah Kelurahan Manisrejo Kabupaten Magetan - Ratnaningrum, Cahyanti Dwi; , Siti Arifah, S.Kep., M.Kes (2016)
Children who are still in primary school are usually very fond of the game. At this time the child is affected by the games were done online or via the Internet. Most children who have been cool to play electronic games will forget him. Children do not want to care about the environment even though they have their own world. The purpose of this study is to describe how the impact of electronic games in school age children in the Urban Village Manisrejo, Magetan. This research is descriptive and analytical. Research is population of children who play electronic games in Internet cafes Manisrejo village, Magetan some 90 children for one month while the sample number of 25 children who play electronic games at an internet cafe in the Village Manisrejo, Magetan is determined using the accidental sampling technique. Collecting data using a questionnaire, while data analysis using descriptive analysis. Conclusion of the study is the description of the amount of sleep children who play electronic games in school age children in the Urban Village Manisrejo, Magetan mostly 8-9 hours according to the needs of children aged 10-12 years (64%), picture delays to school attendance of children in school age children in Urban Village Manisrejo, Magetan shows most children experience delays attendance to school (56%), and a description of the activity of running the dawn prayer at school-age children in the Village Manisrejo, Magetan showed most respondents did not carry out the activity of the dawn prayer (100%).